2018
DOI: 10.1111/1749-4877.12324
|View full text |Cite
|
Sign up to set email alerts
|

Are the number and size of scales in Liolaemus lizards driven by climate?

Abstract: Ectothermic vertebrates are sensitive to thermal fluctuations in the environments where they occur. To buffer these fluctuations, ectotherms use different strategies, including the integument, which is a barrier that minimizes temperature exchange between the inner body and the surrounding air. In lizards, this barrier is constituted by keratinized scales of variable size, shape and texture, and its main function is protection, water loss avoidance and thermoregulation. The size of scales in lizards has been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…In our study, we found a strong positive relationship between scale size and body size in A. cristatellus (scale size scales isometrically with body size). This result is not unexpected, as the scale‐size to body‐size link has been documented (predominantly on the interspecific scale) in many lizards groups, such as Liolaemus (Tulli & Cruz, ), Sceloporus (Oufiero et al. ) and Anolis (Wegener et al.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…In our study, we found a strong positive relationship between scale size and body size in A. cristatellus (scale size scales isometrically with body size). This result is not unexpected, as the scale‐size to body‐size link has been documented (predominantly on the interspecific scale) in many lizards groups, such as Liolaemus (Tulli & Cruz, ), Sceloporus (Oufiero et al. ) and Anolis (Wegener et al.…”
Section: Discussionsupporting
confidence: 54%
“…In our study, we found a strong positive relationship between scale size and body size in A. cristatellus (scale size scales isometrically with body size). This result is not unexpected, as the scale-size to body-size link has been documented (predominantly on the interspecific scale) in many lizards groups, such as Liolaemus (Tulli & Cruz, 2018), Sceloporus (Oufiero et al 2011) andAnolis (Wegener et al 2014). Interestingly, most studies do not measure the actual size of the scale, but instead count the number of scales along a defined transect on the skin and use the inverse of these scale counts as a proxy of scale size (Kerfoot, 1970;Thorpe & Baez, 1987;Malhotra & Thorpe, 1997;Oufiero et al 2011;Wegener et al 2014).…”
Section: Body Size and Scale Morphologymentioning
confidence: 55%
See 3 more Smart Citations